2020
DOI: 10.1038/s41598-020-57921-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally sensitive grain-size component records and its response to climatic and anthropogenic influences in Bosten Lake region, China

Abstract: Using 137 cs and 210 Pb dating and multi-proxy evidence from a 41-cm sediment core from Bosten Lake in China, the responses of sediment grain size to environmental changes were reconstructed over the past 150 years. After the end of the Little Ice Age, the climate of the Bosten Lake region became warmer and drier, and the lake water level decreased. The results indicated that the lowest water storage periods occurred at approximately 1920-1930 AD. Decreases in the Siberian High intensity and water vapour trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 76 publications
0
10
0
1
Order By: Relevance
“…The catchment area of the basin is 5.5-105 km 2 . The rivers that flow into Bosten Lake are the Kaidu River, and the Huangshui River, and only the Kaidu River is perennial [13]. The Kaidu River originates from the snowy mountains in the west; its water source is supplied by mountain precipitation and meltwater of ice and snow, and the total length of this river is 513 km [41], with an annual runoff of 3.99 billion cubic metres [42].…”
Section: Geographic Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The catchment area of the basin is 5.5-105 km 2 . The rivers that flow into Bosten Lake are the Kaidu River, and the Huangshui River, and only the Kaidu River is perennial [13]. The Kaidu River originates from the snowy mountains in the west; its water source is supplied by mountain precipitation and meltwater of ice and snow, and the total length of this river is 513 km [41], with an annual runoff of 3.99 billion cubic metres [42].…”
Section: Geographic Backgroundmentioning
confidence: 99%
“…The research on Bosten Lake mainly focuses on the changes in the lake water level [9], as well as the physical, chemical and biological characteristics of water bodies, such as water and salt dynamics [10], weathering processes and water quality [11], and water microorganisms [12]. The regional paleoclimate and paleoenvironmental characteristics are reconstructed from the aspects of lake sediment grain size [13] and carbon isotopes [14]. Previous researchers conducted fruitful research on paleoenvironmental changes using lake sediment [15][16][17][18][19][20][21][22] and the modern ecology and environment of Bosten Lake [23][24][25][26], especially for surface sediments, e.g., studies of organic pollution [23,27], bacterial community [28][29][30][31], and PTE pollution [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In lacustrine sediments, the correlation between magnetic susceptibilities measured at different frequencies is very good, and the correlation coefficient (r) can exceed 0.99 (p < 0.001), indicating that increasing magnetic susceptibility is related to an increase in the content of magnetic minerals. Previous studies have shown that MS can be used to reflect the variations in the intensity of human activities [58][59][60]. The intensification of human activities has led to the enrichment in ferromagnetic materials of surface materials entering the lake, which has led to a significant increase in magnetic susceptibility since 1970 AD.…”
Section: Discussionmentioning
confidence: 99%
“…The proxies that are sensitive to precipitation changes in lake sediments are different in different regions, for example, biomarker compounds [34,71,72], Rb/Sr ratios [73], and magnetic susceptibility [74] are sensitive to changes in precipitation in some regions. In addition, the environmental information reflected by the grain size of lake sediments in different regions is also different, for example, it can reflect wind intensity and dust transport [75,76], riverine input [77] and lake water level changes [78]; however, it can be used as a useful indicator for quantitative reconstruction of long-term paleoprecipitation in the region of Lake Ta-Lung-Chi in Tianshan Mountains. The total precipitation from April to September showed a significant downward trend from 1930 to 1975, after which an overall increasing trend began.…”
Section: Discussionmentioning
confidence: 99%